Transmisi Budaya dan Konsep Konfusianisme dalam Kurikulum Pelajaran Agama Konghucu di Indonesia - Hun, Siem Hong (Indonesian Character Journal, 2025)
This paper examines the spread and development of Confucian teachings in Indonesia that evolved into the Konghucu religion through the process of localization and institutionalization. Using a descriptive qualitative research method with inductive elaboration, the paper analyses the core concepts of the Konghucu religion’s educational curriculum in Indonesia, finding that the concepts of Godhead and the universe, the cultivation of morals and ethical norms, rituals and religious practices as well as the indigenization of Confucian teachings are the most prominent ones taught as Konghucu religious education. These elements demonstrate the unique position of Confucianism in Indonesian society and its important role in promoting social harmony, moral and ethical development, and cultural transmission, which ultimately has a positive impact on the education of national integration of the Republic of Indonesia.